Neil Flambé and the Crusader's curse - Sylvester, Kevin (Sylvester, Kevin. Neil Flambé capers, 2014)
The sudden disappearance of fifteen-year-old Neil Flambé's skills as a world-class chef leads to the closing of his restaurant, a cook-off to save his reputation, and the discovery of a dark curse that has plagued Flambé cooks for centuries.